Bipolar Thermofusion BiClamp 150 in Thyroidectomy: A Review of 1156 Operations - Pniak, Tomáš (Hindawi Publishing Corporation, 2014)
Objectives. To compare the bipolar thermofusion BiClamp 150 with conventional ligature techniques for thyroid gland surgery, and report the advantages/disadvantages of both techniques. Methods. In this retrospective comparative study, all thyroid gland operations performed in the ENT Clinic Faculty Hospital Ostrava from 2006 to 2013 were included (1156 operations, 2122 lobes). Patients were categorized into two groups according to the type of vessel sealing method used, group I (BiClamp, n = 819 operations) and group II (conventional ligature, n = 337 operations). The number of revision surgeries due to wound hematoma was recorded as a bleeding event. Statistical analysis of the complication rate (bleeding rate, recurrent nerve palsy) and time of duration was performed. Results. The rate of revision surgery performed due to postoperative wound hematoma was significantly lower in group I (15/819, 1.83%) compared with group II (14/337, 4.15%) (P = 0.022). There was no statistically significant difference in the frequency of recurrent laryngeal nerve palsy between groups I and II (P = 0.36). The average surgery time was significantly shorter in group I (P < 0.001). Conclusion. Bipolar thermofusion BiClamp is an effective vessel sealing method that leads to a significant reduction in postoperative wound bleeding rates and reduces surgical time compared with conventional vessel ligature.